PENGARUH KEAKTIFAN BERORGANISASI TERHADAP KOMPETENSI INTERPERSONAL MAHASISWA PENDIDIKAN AKUNTANSI FKIP UNS - Yaqin, Isa Ulinuha Ainul; Santoso, Sigit; -, Sohidin (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objective of this research is to investigate whether or not the activeness in organization has an effect on the interpersonal competency of the students of Accounting Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University in 2016. This research used the quantitativeÂ  research method. Its population was all of the students as many as 246 of Accounting Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University in 2016. The samples of research consisted of 56 Class 2014 students of Class A and Class B and were taken by using the purposive sampling technique. The data of research were collected through questionnaire and analyzed by using the simple linear regression analysis assisted with the computer program of SPSS Version 23 for Window. The result of research shows that the activeness in organization has a positive and significant effect on the interpersonal competency of the students of Accounting Education Department of the Faculty of Teacher Training and Education, Sebelas Maret University in 2016 as indicated by the value of r = 0.624, the value of r2 = 0.377, and the value of t count= 4.140 which was greater than that of ttable = 1.671 at the significance level of 5%. The regression equation is Y = 34.805 + 0.536X.Keywords: Activeness in organization, interpersonal competency, EducationABSTRAKPenelitian ini bertujuan untuk mengetahui ada tidaknya pengaruh keaktifan berorganisasi terhadap kompetensi interpersonal mahasiswa Pendidikan Akuntansi FKIP UNS Tahun 2016. Penelitian ini menggunakan metode penelitian kuantitatif. Populasi dalam penelitian ini adalah seluruh mahasiswa Pendidikan Akuntansi FKIP UNS Tahun 2016 yang berjumlah 246 mahasiswa. Sampel yang terpilih berjumlah 56 mahasiswa, yaitu mahasiswa angkatan 2014 kelas A dan kelas B dengan menggunakan teknik purposive sampling. Pengumpulan data penelitian dilaksanakan dengan menggunakan angket/kuesioner. Analisis data menggunakan teknik analisis regresi linier sederhana dengan program SPSS versi 23 for window. Hasil penelitian ini adalah terdapat pengaruh yang positif dan signifikan antara keaktifan berorganisasi terhadap kompetensi interpersonal mahasiswa Pendidikan Akuntansi FKIP UNS Tahun 2016. Hal ini ditunjukkan dengan harga r sebesar 0,614 dan r2 sebesar 0,377, serta thitung> ttabelatau 4,140 > 1,671 pada taraf signifikansi 5%. Persamaan regresi adalah Y = 34,805 + 0,536X.Kata kunci : Keaktifan Berorganisasi, Kompetensi Interpersonal, Pendidikan